Institutional development and resource development: the case of Canada's Indigenous peoples. Issue 1 (2nd January 2018) - Rodon, Thierry
ABSTRACT: In debates around the so-called resource curse, one camp argues that resource development corrupts economies and institutions, while the other camp claims institutions can mediate the impact of resource development. This article explores whether land claims agreements (LCAs) in the Canadian Arctic have helped Indigenous peoples improve development outcomes for their communities. We analyse the institutional frameworks created by LCAs in four case studies: the Cree of Eeyou Istchee, the Inuit of Nunavik, the Inuit of Nunavut and the Inuit of Nunatsiavut. We find a positive institutional effect on capacity to control and benefit from resource development for one: the Cree of Eeyou Istchee.